Relearning and Retaining Personally-Relevant Words using Computer-Based Flashcard Software in Primary Progressive Aphasia - Evans, William S.; Quimby, Megan; Dickey, Michael Walsh; Dickerson, Bradford C. (Frontiers in Human Neuroscience, 2016)
Although anomia treatments have often focused on training small sets of words in the hopes of promoting generalization to untrained items, an alternative is to directly train a larger set of words more efficiently. The current case report study reports on a novel treatment for a patient with semantic variant Primary Progressive Aphasia (svPPA), in which the patient was taught to make and practice flashcards for personally-relevant words using an open-source computer program (Anki). Results show that the patient was able to relearn and retain a large subset of her studied words over a 20-month period. At the end of treatment, she showed good retention for 139 studied words, far more than the number typically treated in svPPA studies. Furthermore, she showed evidence of stimulus generalization to confrontation-naming tasks for studied items, and of relearning forgotten items with additional practice. This case represents a successful example of patient-centered computer-based asynchronous telepractice. It also illustrates how data captured from computer-based treatments can provide powerful “practice-based evidence,” obtained during routine clinical care.